2011
DOI: 10.1080/09540121.2010.543884
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of HIV antiretroviral treatment persistence in a commercially insured population in the United States

Abstract: This study examined factors associated with persistence (time from initiation to discontinuation of treatment) on initial antiretroviral (ARV) therapy in commercially insured HIV patients in the United States, a population not well researched. This retrospective analysis of US health insurance claims data from 1 January 2003 to 30 June 2008 included treatment-naive patients aged 18–65 years with an HIV diagnosis receiving ARV therapy consisting of at least two individual nucleoside reverse transcriptase inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 16 publications
9
24
0
Order By: Relevance
“…This result is similar to other longitudinal studies [26, 27]. PIs have a lower number of resistance mutations for reverse transcriptase enzymes compared to NNRTIs, which justifies this drug choice in preventing failure.…”
Section: Discussionsupporting
confidence: 89%
“…This result is similar to other longitudinal studies [26, 27]. PIs have a lower number of resistance mutations for reverse transcriptase enzymes compared to NNRTIs, which justifies this drug choice in preventing failure.…”
Section: Discussionsupporting
confidence: 89%
“…43,44 We also found that women were more likely to discontinue ART in all 3 models, consistent with other studies on ART persistence. 22,28 More frequent HIV medication side effects and toxicity reported by women compared with men 45,46 may account for the lower ART persistence observed in women. We found that injection drug use in the past 12 months was associated with significantly increased odds of discontinuing ART, which is consistent with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…1821 Examinations of the prevalence and predictors of ART discontinuation have demonstrated that certain patients are more likely to discontinue ART. Substance use, 22 injection drug use, 23 disease severity, 14,22,24,25 younger age, 14,25,26 racial/ethnic minorities, 26,27 female gender, 22,28 unemployment, 28 perceived HIV stigma, 29 fear of discrimination, 30 mental health, 14,24,28,31,32 and side effects 33 have been associated with ART discontinuation. However, these studies lack generalizability since they were conducted on subpopulations of HIV-infected patients, such as patients from 1 or a small group of clinics or hospitals, women only, or patients with a history of substance abuse.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned selection criteria were applied to all medication groups. For ART users, we included only those using valid regimens, defined as those receiving a minimum of three different antiretroviral ingredients [5, 15, 16]. ACEI and ARB users were combined into one group.…”
Section: Methodsmentioning
confidence: 99%